2019
DOI: 10.1096/fj.201900238rr
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiota contributes to altered glucose metabolism in simulated microgravity mouse model

Abstract: Exposure to space environment induces alterations in glucose and lipid metabolism that contribute to muscular atrophy, bone loss, and cardiovascular disorders. Intestinal microbiota is also changed, but its impact on spaceflight‐related metabolic disorder is not clear. We investigated the relationship between glucose metabolic changes and gut dysbiosis in a hind limb‐unloading (HU) mouse model, a well‐accepted ground‐based spaceflight analog. Impaired body weight gain, glucose intolerance, and peripheral insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 53 publications
0
42
0
1
Order By: Relevance
“…However, it remains a fact that during spaceflights astronauts and cosmonauts eat less than on Earth, probably for several reasons, including but not limited to cultural habits (but the international coordination imposed by ISS is changing this aspect), the palatability of foods (still not comparable to what is available on Earth), space motion sickness, changes in light-dark cycle and appetite-regulating hormones, and, in general, stress (Laurens et al, 2019). Though the reasons are not entirely clear, impaired glucose and lipid metabolism, with insulin resistance and glucose intolerance, are also frequently observed in both spaceflights and ground-based microgravity analogs, representing a serious concern for the general health of space travelers (Tobin et al, 2002;Hughson et al, 2016;Wang Y. et al, 2019).…”
Section: Gut Microbiome and Metabolic Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it remains a fact that during spaceflights astronauts and cosmonauts eat less than on Earth, probably for several reasons, including but not limited to cultural habits (but the international coordination imposed by ISS is changing this aspect), the palatability of foods (still not comparable to what is available on Earth), space motion sickness, changes in light-dark cycle and appetite-regulating hormones, and, in general, stress (Laurens et al, 2019). Though the reasons are not entirely clear, impaired glucose and lipid metabolism, with insulin resistance and glucose intolerance, are also frequently observed in both spaceflights and ground-based microgravity analogs, representing a serious concern for the general health of space travelers (Tobin et al, 2002;Hughson et al, 2016;Wang Y. et al, 2019).…”
Section: Gut Microbiome and Metabolic Healthmentioning
confidence: 99%
“…In addition to the design of balanced diets enriched in prebiotics, probiotics-based countermeasures could also be taken into consideration. For example, in a recent spaceflight analog study based on HU mouse model, Wang Y. et al (2019) have shown that the supplementation of Bifidobacterium spp. suppressed endotoxemia and liver inflammation, and improved glucose tolerance.…”
Section: Gut Microbiome and Metabolic Healthmentioning
confidence: 99%
“…Similarly, gut dysbiosis has been reported in astronauts and experimental animals maintained in unloading conditions. Indeed, both microgravity and space radiation predispose to different space related disorders, most being accompanied by immune system dysregulation [41,42]. In fact, in healthy conditions, the GM plays a crucial role in the maintenance of the host’s physiological conditions by modulating its immunity.…”
Section: Gut Microbiota (Gm) Influence On Disorders Characterizedmentioning
confidence: 99%
“…Igualmente existen alteraciones en la motilidad, microbiota intestinal, metabolismo de glucosa y lípidos (89,90) , daño de las vellosidades intestinales e interrupción en las uniones celulares epiteliales por la expresión de la proteína proapoptótica Bax y disminución de Bcl2; alterando de esta manera su función defensiva, homeostasis y el riesgo de contraer enfermedades inflamatorias intestinales (76,91,92,93) por el aumento de citosinas y disminución de la inmunoglobulina secretora (IgA) (76) .…”
Section: Sistema Digestivounclassified